Ascending the summit: national laboratories as the upgrading path for driving national value chains - Zhenzhen Chen; Yu He; Fei Guo (Journal of Applied Economics, 2025)
With the domestic trend of value chains becoming increasingly apparent, innovation-driven growth is crucial for a higher position in various industries. This study analyzes the effect of building national laboratories on the national value chains’ position (the average propagation length) by employing an interregional input-output table of 42 industrial sectors in China’s 31 provinces and applying the fixed-effects model and the intermediary effect model. Empirical findings suggest that building national laboratories positively influences the national value chains’ position. Influence channels indicate that national laboratories advance national value chains via the innovation chain (i.e. innovative platforms, R&D investment, sci-tech achievements, and innovation performance). Industrial upgrading (industrial rationalization, industrial advancement, and industrial ecology) has the intermediary and threshold effect between national laboratories and the national value chains’ position. Lastly, the positive effect is higher in high-tech manufacturing, regions with more state key laboratories, forward linkages, southern regions, and better business environments.